Management Of Fluid Resuscitation In Burn Wounds - Kirene Dwinilasari Paemba; Berry Erida Hasbi; Muhammad Wirawan Harahap (Sean Institute, 2024)
The World Heath Organization (WHO) states that women in the Southeast Asia region have a high incidence of burns, which is 27% of the total number globally. The Burn Incidence Fact Sheet of the American Burn Association (ABA) states that in 2016, 486,000 people sought burn care in the United States. Most burns are small with 67% occupying less than 10% of the total body surface area according to the National Burn Repository of the ABA . Resuscitation is needed to restore respiratory function and blood circulation in someone who has experienced cardiac or respiratory arrest. This research method uses a literature review with a narrative review design. Based on the review obtained, crystalloids are the type of fluid that is widely used for burn patient therapy and for colloid fluids that are widely used are 20% albumin. The importance of calculating the need for fluid intake with fluid output is seen from urine output in patients using one of the most common formulas, namely the Parkland formula because the amount of fluid entered is higher than the recommended amount indicating the potential risk of excess fluid which can increase complications